Dose delivery reproducibility for PBS proton treatment of breast cancer patients with and without mask immobilization - Yixiu Kang; Martin Bues; Michele Y. Halyard; Lisa A. McGee; Tamara Z. Vern-Gross; William W. Wong; Sameer R. Keole; Carlos Vargas; Sarah E. James; Safia K. Ahmed; James P. Archuleta; Ana K. Ridgway; et al. (Radiation Oncology, 2023)
Abstract Background Setup reproducibility of the tissue in the proton beam path is critical in maintaining the planned clinical target volume (CTV) dose coverage and sparing the organs at risk (OAR). In this study, we retrospectively evaluated radiation therapy dose reproducibility for proton pencil beam scanning (PBS) treatment of breast cancer patients with and without mask immobilization. Methods Ninety-four patients treated between January 2019 and September 2022 with at least one verification CT scan (V-CT) in treatment position were included for this study. All patients were set up with arms up using the Orfit AIO patient positioning system, with (69 patients) or without (25 patients) mask immobilization in chin, neck, shoulder, upper arm, and chest areas. Two to three enface or near enface single field uniform dose PBS beams were optimized using a commercial treatment planning system. Prescription doses were 25 to 60 GyRBE in 5 to 45 fractions. Treatment plan doses re-calculated on V-CTs were compared to the corresponding planned doses. Cumulative doses were also calculated for patients with at least 3 V-CTs by deform and weighted sum doses from V-CTs to corresponding P-CTs. CTV D95%, ipsilateral-lung V40%, esophagus D0.01cc, and heart mean dose were evaluated and reported as percentages of prescription doses. Differences were large dose deteriorations (LDD) if: (1) CTV (V-CT/cumulative D95%) – (Planned D95%) < − 5%; or (2) Ipsilateral-lung (V-CT/cumulative V40%) – (Planned V40%) > 5%; or (3) Esophagus (V-CT/cumulative D0.01cc) – (Planned D0.01cc) > 10%; or (4) Heart (V-CT/cumulative mean) – (Planned mean) > 1.5%. Results On average, V-CT/cumulative and planned CTV/OAR dose parameter differences were less than 2.2%/1.7% and 3.4%/3.7% for masked and maskless patients, respectively. The percentages of patients with at least one CTV or OAR V-CT/cumulative dose LDD were 20.3%/25.0% and 72.0%/54.0% for masked and maskless patients, respectively. Conclusions On average, masked/maskless setups achieved delivered and planned CTV/OAR dose parameters agreed within 2.2%/3.7% for PBS treatment of breast cancer patients in this study. Maskless patients had higher rate of CTV/OAR LDDs compared to masked patients. Dosimetric differences large enough to raise clinical concerns in either group were able to be addressed with replannings.